“TEACHING WRITING NARRATIVE TEXT THROUGH STORY MAP TO THE EIGHTH GRADE STUDENTS OF STATE JUNIOR HIGH SCHOOL 2 OF PALEMBANG” - Yuspar Uzer (Universitas PGRI Palembang, 2015)
Abstract This research entititled “Teaching Writing Narrative Text Through Story Map to the Eighth Grade Students of State Junior High School 2 of Palembang”. The Formulation of the Problems, “Is it effective to teach writing narrative text through story map to the eighth grade students of State Junior High School 2 of Palembang?” The objective of the research was to find out whether or not it is effective to teach writing narrative text through story map to the eighth grade students of State Junior High School 2 of Palembang. The method used is pre – experimental method with the one group pre-test and post-test design. According to Fraenkel and Wallen (2012:236), a single group is measured and observed not only after exposed to a treatment of some short but also before. The population of this research is the eighth grade students of State Junior High School 2 of Palembang consisted of 231 students. A convenience sample is a group of individuals who (conveniently) are available for study for VIII.4 consisted 37 students. Finally, from this research it is found that the pre-test was 77.22 and post test was 79.9. Based on the calculation of the match t-test was higher than the critical of t value the data showed that the calculation of the match t-test was 6.56. It means that the null hypothesis was rejected and consequently alternative hypothesis was accepted. In other words teaching writing narrative text through story map to the eighth grade students of state junior high school 2 of Palembang was effective to increase the students’ writing. Keywords: teaching, writing, story map